Does Government Ownership Affect the Cost of Debt? Evidence from Privatization - Borisova, Ginka; Megginson, William L. (Review of Financial Studies, 2011)
We explore whether government ownership affects the cost of debt using a sample of fully and partially privatized companies. On average across firms, a one-percentage-point decrease in government ownership is associated with an increase in the credit spread, used as a proxy for the cost of debt, by three-quarters of a basis point. However, fully privatized companies exhibit lower credit spreads than partially privatized firms, indicating the cost of a lengthy privatization process. Empirical evidence suggests that these findings result from decreasing government guarantees, firm performance improvements, ownership uncertainty, and bondholder-shareholder conflicts. The Author 2011. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please e-mail: journals.permissions@oup.com., Oxford University Press.